2009
DOI: 10.1073/pnas.0907787106
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals mechanism for short-term and long-term clonal transitions in pandemic Vibrio cholerae

Abstract: Vibrio cholerae, the causative agent of cholera, is a bacterium autochthonous to the aquatic environment, and a serious public health threat. V. cholerae serogroup O1 is responsible for the previous two cholera pandemics, in which classical and El Tor biotypes were dominant in the sixth and the current seventh pandemics, respectively. Cholera researchers continually face newly emerging and reemerging pathogenic clones carrying diverse combinations of phenotypic and genotypic properties, which significantly ham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
422
3
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(463 citation statements)
references
References 38 publications
21
422
3
5
Order By: Relevance
“…An increased expression of RTX toxin in Vc450 at the virulent temperature of 27 1C may allow for increased survival of Vc450 owing to degradation of the host's innate immune system. V. coralliilyticus pathogenicity islands Pathogenic vibrios, like many bacteria, commonly acquire virulence factors via horizontal transfer of bacteriophages and pathogenicity islands (Chun et al, 2009). We identified two novel pathogenicity islands in the genome of Vc450.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased expression of RTX toxin in Vc450 at the virulent temperature of 27 1C may allow for increased survival of Vc450 owing to degradation of the host's innate immune system. V. coralliilyticus pathogenicity islands Pathogenic vibrios, like many bacteria, commonly acquire virulence factors via horizontal transfer of bacteriophages and pathogenicity islands (Chun et al, 2009). We identified two novel pathogenicity islands in the genome of Vc450.…”
Section: Resultsmentioning
confidence: 99%
“…coralliilyticus genome To investigate the presence of potential virulence factors, we performed whole genome sequencing of Vc450 and identified an asymmetrical, two-chromosome structure consistent among all Vibrio genomes examined (Okada et al, 2005;Chun et al, 2009). The larger (C1-3 416 103 bp) and smaller (C2-1 865 911 bp) chromosomes follow a gene distribution pattern typical for vibrios with C1 predominantly carrying genes for viability and growth, and C2 mostly bearing genes for adaptation to environmental change (Makino et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive genetic exchange between co-occurring strains has been previously implied by metagenomic studies of natural populations (Tyson et al, 2004;Konstantinidis and DeLong, 2008), but the fragmented nature of these data sets did not allow robust estimations of the magnitude of the genetic exchange at the wholegenome level or assessment of its ecological consequences (Eppley et al, 2007;Konstantinidis and DeLong, 2008). Recent studies of isolated strains have also reported elevated levels of genetic exchange between pathogenic bacteria such as between distinct Campylobacter species (Sheppard et al, 2008) or within Vibrio cholerae (Chun et al, 2009). However, the genes exchanged in these cases are typically limited to a few environmentally selected functions and show strong biases in terms of spatial location in the genome (Caro-Quintero et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The predicted ORFs were annotated by searching against clusters of orthologous groups (COGs; Tatusov et al, 1997) and SEED databases (Disz et al, 2010). A comparative method was also employed, as described previously by Chun et al (2009), in which target contigs with homology to a query ORF (450% amino-acid sequence over 50% of the length of the gene) were identified using BLASTN. Nucleotide sequences of the query ORF, and selection of target homologous regions, were then aligned using a pairwise global alignment algorithm (Myers and Miller, 1988).…”
Section: Sample Collectionmentioning
confidence: 99%